Etnobotani Masyarakat Suku Lio: Studi Kasus di Desa Waturaka Kawasan Taman Nasional Kelimutu Kabupaten Ende Nusa Tenggara Timur - Veronika Praja Sinta Mbia Wae; Jumilah Gago; Yulius Dala Ngapa (Program Studi Pendidikan Biologi, FKIP Unpas,, 2022)
The purpose of this study was to determine the interaction of the surrounding community with the diversity of plants in the TNK area and to identify the use of plants by the community around TNK. This research was conducted in the Kelimutu National Park area, Ende Regency, East Nusa Tenggara Province and Waturaka Village in May 2021. The tools used in this study, namely: interview guide (questionnaire), stationery, camera, recorder, calculator, machete/machete, flower scissors, label paper, plastic rope, plastic, a list of respondents' questions, and a computer and its equipment. While the materials used in this study were 70% alcohol, plant samples, bamboo sacks and newsprint. The research subjects are the people of Waturaka Village, Kelimutu District, Ende Regency. The objects in this study are medicinal plants in the Kelimutu National Park area and are cultivated by the community in Waturaka Village. The study used a survey method through observation and identification of plants and the determination of respondents by purposive sampling method totaling 250 people, consisting of 65 men and 185 women. The data obtained were analyzed using qualitative descriptive. The results showed that there were 49 species of medicinal plants from 29 families. Leaves are the most widely used plant parts as medicines. Zingiberaceae family has the highest usage percentage of 85%.